Expectations of Future Mathematics Teachers in Relation to the Tutor - Chicote, Rosalino Subtil (2024)
This article discusses the characteristics of tutors desired by future mathematics teachers. The research aimed to identify future Mathematics teachers’ expectations regarding tutors’ characteristics during the formative process. We collected data through interviews with eight future mathematics teachers in initial training, and they attended the pedagogical internship in Mathematics Teaching, one of the curricular activities of the 4th year of the degree course in Mathematics Teaching at a Mozambican University. The data analysis started from a codification focused on interpreting the empirical indicators and constructing new codes that were subsequently aggregated into categories. From the results, we highlight that future mathematics teachers have expectations regarding tutors, preferring that they are considered as ‘colleagues’ of their profession. They have the following characteristics: a predisposition for communication, a predisposition to a host, and a predisposition for teaching and learning.